User perceptions of surgical antimicrobial prophylaxis guidelines in orthopaedic surgery in a tertiary Australian hospital. - Sarah Hassan; Vincent Chan; Julie E Stevens; Ieva Stupans; Juliette Gentle (PLoS ONE)
Background Surgical antimicrobial prophylaxis remains the most common indication for antimicrobial use in Australian hospitals. Despite efforts to improve practice, adherence to guideline recommendations continues to be suboptimal across surgical disciplines, including orthopaedics. The Therapeutic Guidelines: Antibiotic v16 currently advocates for single dose prophylaxis for open reduction internal fixation (ORIF) procedures. Audits undertaken in one Australian tertiary hospital have identified low levels of adherence to this recommendation. It is unclear as to why guidelines are not adhered to in this setting. Aim To understand the factors that influence multidose prescribing for ORIF procedures and the barriers and enablers to guideline use in an Australian tertiary hospital. Materials and methods Interviews (focus groups and one-on-one sessions) were held with orthopaedic surgeons (consultants), orthopaedic registrars, pharmacists, and anaesthetists from a tertiary public hospital in Australia. The Theoretical Domains Framework (TDF) was used to analyse results. Results Six focus groups and three one-on-one interviews were conducted. Data were mapped to 12 TDF domains. Although clinicians were aware of guideline recommendations, this alone did not encourage the use of single dose prophylaxis. The decision to prescribe postoperative antibiotics was influenced by a combination of patient and environmental factors as well as fear of infection development. The lack of guideline specificity was commonly highlighted as a barrier to guideline use, as well as lack of agreement with guideline content. Enablers to guideline use included education that was targeted and repetitive, as well as improved dissemination of guidelines. Conclusion There are myriad factors that influence the decision to prescribe postoperative antibiotics for ORIF procedures. By understanding the social and cultural context of a local setting and the barriers and enablers that pertain to an environment, interventions can be developed to enhance guideline use, thereby improving antimicrobial prescribing.